IMPROVED THERMAL DESIGN FOR REFRIGERANT IN PLATE BUTTER-MAKING MACHINE - Evgeny Alekseevich Chebotarev; Aleksandr Vladimirovich Malsugenov (Вестник Северо-Кавказского федерального университета)
The item focuses on a new approach to the mathematical description of cooling in a plate-type scraper heat exchanger in butter-making machines, which allows improving the thermal design.